Allogenic Umbilical Cord Tissue for Treatment of Knee Osteoarthritis. Issue 3 (3rd September 2022) - Gupta, Ashim; Maffulli, Nicola
Abstract : Interest in use of perinatal allogenic tissues including clinical-grade minimally manipulated umbilical cord tissue-derived allograft formulations to treat knee osteoarthritis (OA) patients is increasing. Limited studies have characterized these formulations and evaluated their safety and efficacy in knee OA patients. We developed such formulation and reported the presence of growth factors, cytokines, hyaluronic acid, and exosomes. We reported that its administration is safe, and resulted in 50% pain reduction and improvement in knee injury and osteoarthritis outcome score (over 10%) and 36-item short form survey (25%). Another study reported no adverse events post injection of similar formulation and statistically significant ( P <0.001) improvement in visual analog scale and Western Ontario and McMaster Universities Osteoarthritis Index scores and reduction in medication usage in patients (77.8%). We also summarized the clinical trials registered on ClinicalTrials.gov utilizing umbilical cord tissue for knee OA treatment. In conclusion, available studies are preliminary but pave the way to higher level appropriately powered investigations, and these formulations should be considered as nonoperative alternative to manage knee OA.